Atrioventricular Conduction in Mesial Temporal Lobe Seizures - Pensel, Max C.; Basili, Luca M.; Jordan, Arthur; Surges, Rainer (Frontiers in Neurology, 2021)
Purpose: Asymmetric cerebral representation of autonomic function could help to stratify cardiac complications in people with epilepsy, as some seizures are associated with potentially deleterious arrhythmias including bradycardia and atrioventricular (AV) conduction block. We investigated seizure-related changes in AV conduction and ascertained whether these alterations depend on the hemisphere in mesial temporal lobe epilepsy (mTLE). Methods: EEG and ECG data of people with pharmacoresistant mTLE undergoing pre-surgical video-EEG telemetry with seizures independently arising from both hippocampi, as determined by intracranial depths electrodes were reviewed. RR and PR intervals were measured using one-lead ECG. Statistics were done with paired student's t-tests and linear regression analysis. Data are given as mean ± SD. Results: Fifty-six seizures of 14 patients (5 men, age 34.7 ± 9.8 years) were included (2 seizures per hemisphere and patient). There were no differences of absolute PR intervals and HR before and during unilateral ictal activity between left- and right-sided hippocampal seizures. Peri-ictal modulation of AV conduction, however, appeared greater with left-sided seizures, as the slope of the PR/HR correlations was significantly steeper with seizures originating in the left hippocampus. PR lengthening >200 ms or full block did not occur in any seizure. Conclusions: Our data show that on average, PR intervals shortens with mesial temporal lobe seizures with more prominent effects in seizures with left-sided onset, supporting the notion of lateralized cerebral control of cardiac function. The clinical relevance of this subtle finding is unclear but may indicate a lateralized susceptibility to seizure-related AV node dysfunction in mTLE.